2006
DOI: 10.3168/jds.s0022-0302(06)72084-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Controlled Milk Feeding of Group-Housed Calves: The Effect of Milk Allowance and Weaning Type

Abstract: Calves fed by computer-controlled milk feeders are often weaned gradually by reducing the size of the milk portions. However, reducing the number of milk portions instead may lower calves' occupation of the milk feeder and stimulate their concentrate intake, especially when they are offered a high milk allowance. Before weaning, but not during weaning, the calves on low milk allowance occupied the milk feeder more, consumed more concentrates, and had a lower daily gain. There was no interaction between milk al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 8 publications
9
41
0
8
Order By: Relevance
“…However, with these conventional weaning systems there are often problems, because heavier calves tend to obtain more MR and disturb the smaller calves when they are drinking (Hepola, 2003). The calves fed by a computer-controlled feeder can gradually be weaned, for instance, over a couple of weeks, and weaning is typically done by reducing the size of the MR portions and/or reducing the number of MR portions (Jensen, 2006). In the present study we reduced gradually both the size and the number of the portions over a couple of weeks but, still, the F calves had difficulties in the weaning period and their growth slowed down remarkably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with these conventional weaning systems there are often problems, because heavier calves tend to obtain more MR and disturb the smaller calves when they are drinking (Hepola, 2003). The calves fed by a computer-controlled feeder can gradually be weaned, for instance, over a couple of weeks, and weaning is typically done by reducing the size of the MR portions and/or reducing the number of MR portions (Jensen, 2006). In the present study we reduced gradually both the size and the number of the portions over a couple of weeks but, still, the F calves had difficulties in the weaning period and their growth slowed down remarkably.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning is Available online at www.sciencedirect.com Livestock Science 113 (2008) 302 -306 www.elsevier.com/locate/livsci typically done by reducing the size of the MR portions and/or reducing the number of MR portions (Jensen, 2006). With a computer-controlled system it is possible to wean calves gradually, so the transition from MR to solid feed is easier than by conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that growth rates on our (Bascom et al, 2007). In another study, Jersey calves fed a 24% CP and 19% fat MR grew at a rate of 0.594 kg/d (Jensen, 2006). Klotz and Heitmann (2006) reported an ADG of 0.530 kg/d for Jersey calves fed a 23% CP and 17.5% fat MR.…”
Section: Growthmentioning
confidence: 92%
“…In similar studies, Borderas et al (2009) andJensen (2006) also observed a decrease in milk consumption and an increase in concentrate consumption in calves raised in breeding systems that used an automatic calf feeder after 15 days of age. In calves up to 30 days old, the nutrients are supplied by milk.…”
Section: Resultsmentioning
confidence: 71%